2008
DOI: 10.1117/12.839082
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of vortex generator jets for conical diffuser separation control using PIV

Abstract: Vortex generator jets (VGJs) have been recognized as an effective active control method for the flow separation. To investigate its mechanism in conical diffuser, PIV was used to study the interaction of VGJs with freestream in this study. A conical diffuser model, with divergence angle of 14° was used. The jet holes were drilled with pitch angle of 30° and skew angle of 90°. At several streamwise locations, two-dimensional traverses were set up to obtain the velocity distribution and vorticity in the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…They found that fins restrain the low-frequency pressure amplitude throughout the whole cavitation number range [5]. Yonghui Xie et al studied the vortex generated by VGJ(vortex generator jet) and found that the steady jets create vortices that swept the low momentum fluid up from the boundary layer while transporting high momentum mainstream fluid towards the wall, thus providing the ingredients for flow control [6].…”
Section: Introductionmentioning
confidence: 99%
“…They found that fins restrain the low-frequency pressure amplitude throughout the whole cavitation number range [5]. Yonghui Xie et al studied the vortex generated by VGJ(vortex generator jet) and found that the steady jets create vortices that swept the low momentum fluid up from the boundary layer while transporting high momentum mainstream fluid towards the wall, thus providing the ingredients for flow control [6].…”
Section: Introductionmentioning
confidence: 99%